2006
DOI: 10.1103/physrevb.74.075425
|View full text |Cite
|
Sign up to set email alerts
|

Microwave absorption by an array of carbon nanotubes: A phenomenological model

Abstract: A simple model to explain microwave-induced heating of carbon nanotubes ͑CNTs͒ through transformation of electromagnetic energy into mechanical vibrations is proposed and analyzed. The model provides a way to understand recent observations of heating of CNTs exposed to microwaves in the range of 2 -20 GHz. It is shown that transverse vibrations of CNTs during microwave irradiation can be associated with parametric resonance, as occurs in the analysis of acoustic experiments on forced longitudinal vibrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 28 publications
0
53
0
Order By: Relevance
“…[16] There are basically two possible ways to take advantage of MPs/NPs for immunization purposes. One way consists of 70 encapsulating the antigen inside liposomes [17,18] or inside organic biodegradable polymers, such as poly(lactic acid) (PLA), poly(lactic-co-glycolic acid) (PLGA), [19][20][21][22][23][24] disulfide cross-linked polyacrylates, [25] or polysaccharides, such as pullulan [26] and chitosan. [27][28][29] This way, the particles can easily reach cytosol, where they are degraded, thus releasing the antigen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] There are basically two possible ways to take advantage of MPs/NPs for immunization purposes. One way consists of 70 encapsulating the antigen inside liposomes [17,18] or inside organic biodegradable polymers, such as poly(lactic acid) (PLA), poly(lactic-co-glycolic acid) (PLGA), [19][20][21][22][23][24] disulfide cross-linked polyacrylates, [25] or polysaccharides, such as pullulan [26] and chitosan. [27][28][29] This way, the particles can easily reach cytosol, where they are degraded, thus releasing the antigen.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that CNTs absorb microwave energy because of their structure, [69,70] allowing them to react more easily when using microwaves than when using conventional heating. In fact, microwave-assisted 300 chemistry has become a very attractive and useful tool for the fast and effective functionalization of CNTs in recent years.…”
mentioning
confidence: 99%
“…One property that only belongs to the metallic CNTs is the ability to conduct surface plasmon (SP) waves [3,4,6,7,10]. Also, CNTs have been extensively explored for potential applications in electromagnetic shielding or absorbing materials [5,8,11,12]. Ye et al [5] proposed a simple phenomenological model to explain microwave-induced heating of CNTs through transformation of electromagnetic energy into mechanical vibrations.…”
Section: Introductionmentioning
confidence: 99%
“…Also, CNTs have been extensively explored for potential applications in electromagnetic shielding or absorbing materials [5,8,11,12]. Ye et al [5] proposed a simple phenomenological model to explain microwave-induced heating of CNTs through transformation of electromagnetic energy into mechanical vibrations. It has been shown that CNTs display strong microwave absorbing properties and even though several theories have been offered, the mechanism of nanotube-microwave interaction is still not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, another potential source of localized superheating should be considered, namely, the generation of gas plasma from absorbed gases (particularly H 2 ) in CNTs, under the microwave irradiation, which has been reported in some cases (Imholt et al 2003). A simple model was proposed by Ye and coworkers (Ye et al 2006), to explain microwave-induced heating of CNTs, through transformation of electromagnetic energy into mechanical vibrations. Within this model, CNTs subjected to microwave irradiation undergoes ultraheating due to a transverse parametric resonance, which arises from the polarization of CNTs in the microwave field.…”
Section: Mechanism Of the Carbon Nanotube-microwave Interactionmentioning
confidence: 99%